Effects of soil temperature on a coupled photosynthesis-stomatal conductance model for four boreal tree species - Cai, Tiebo (My University, 2000)
In order to examine the effects of soil temperature on a coupled photosynthesis-stomatal conductance model, seedlings of trembling aspen (Populus tremuloides Michx), jack pine (Pinsu banksiana Lamb. ), black spruce (Picea Mariana (Mill) B.S.P.) and white spruce {Picea glauca (Moench) Voss.) were grown over a wide range of soil temperatures from 5 °C to 35 “C. Temperature, light and CO2 response curves of foliar gas exchange were measured four months after the start of the treatment. The results showed that the four boreal tree species had very similar cardinal soil temperatures for key model parameters (i.e., Vcmax, Jmax). The key parameters of the model showed dual soil temperature symmetry; below-ground and above-ground temperature symmetry, and low and high temperature symmetry. In the below-ground and above-ground temperature symmetry, the key model parameters responded to soil temperature in a similar manner as to leaf temperature. For low and high soil temperature symmetry, the symmetry was not perfect, with steeper slope at the higher-than-optimum temperature range, which indicated the photosynthetic machinery of the four boreal trees was suppressed more at high soil temperatures than at low soil temperatures. The effects of soil temperature on key model parameters were modeled using three different equations. Three equations fitted the measured key model parameters well, but only the bio-chemical equation showed a specific pattern for the equation parameters between the four species. Soil temperature had no effects on R^, the daytime respiration that continues in light. It was speculated that after four months of soil temperature treatments, the four boreal tree species acclimated to different soil temperature conditions by optimizing allocation of nitrogen investment into different functional photosynthetic components and balancing water use efficiency and nitrogen use efficiency.
Keywords: Soil temperature; Photosynthesis; Stomatal conductance; Jack pine; Black spruce; White spruce